STRATEGI PENINGKATAN OBJEKTIVITAS PENILAIAN KINERJA MELALUI PENGUATAN SISTEM MONITORING DAN EVALUASI DI SEKRETARIAT DEWAN PERTIMBANGAN PRESIDEN - Michael Iimmanuel Hutagalung; Yayan Nuryanto; Selvi Centia (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
Objectivity in performance assessment is a crucial indicator in the success of bureaucratic reform; however, its application often faces structural constraints within supporting units of high-state institutions. This research aims to analyze the barriers to the implementation of the Government Agency Performance Accountability System (SAKIP) and to formulate intervention strategies at the Secretariat of the Presidential Advisory Council (Setwantimpres). Utilizing a descriptive qualitative method, the research found a disparity between planning documents (de jure) and the reality of field workloads (de facto), which triggers window dressing practices. Furthermore, the validity of scores is distorted by recency effect bias and the ewuh pakewuh culture. As a concrete solution, this research formulates a revitalization of performance instruments that transforms 10 service elements into 25 measurable quality statements, as well as the formulation of a Technical Guideline Booklet. This intervention is designed to shift the assessment paradigm from subjective assumptions to evidence-based assessment through a standardized service detail validation mechanism.